A joint analysis of environmental and economic performances of closed-loop supply chains under carbon tax regulation. (August 2020) - Dou, Guowei; Cao, Kaiying
Highlights: Remanufacturing does not necessarily protect the environment. Collection rate is piecewise monotonous in the tax price and emission intensity. The retailer collection can be both environmentally and economically better off. Reducing the emission intensity of new products may harm the environment. Two tax prices can be set by the regulator with one subsidy. Abstract: Under carbon tax regulation, we jointly measure the environmental and economic performances of three closed-loop supply chains, where remanufacturing is implemented through the reverse channels of retailer collection, manufacture collection, and a third-party collection. The equilibrium results for each supply chain are derived and the impacts of emission-related factors are characterized. Through numerical study, we explore the impacts of the emission intensities of both new and remanufactured products on the entire emissions. Also, the government's policy concerning environmental protection is discussed. The results show that the collection rate and the first-period product quantity are piecewise monotonous related to the tax price and emission intensities. Either the manufacturer collection or the retailer collection can be the most eco-efficient revers channel while the third-party collection is the least-preferred. The retailer collection can be both environmentally and economically better off to achieve a Pareto-improvement. Otherwise, when the manufacturer collection is the most eco-efficient reverse channel, it can be motivated by the government through subsidizing. Interestingly, the numerical studies show that reducing the emission intensity of remanufactured products can be eco-efficient, while lowering the emission intensity of new products may do harm to the environment. Besides, with one subsidy, two tax prices can be set by the government, among which the higher tax price leads to better environmental sustainability.